2021
DOI: 10.11646/zootaxa.4910.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A revision of the shield-back katydid genus Neduba (Orthoptera: Tettigoniidae: Tettigoniinae: Nedubini)

Abstract: The Nearctic shield-back katydid genus Neduba is revised. Species boundaries were demarcated by molecular phylogenetic analysis, morphology, quantitative analysis of calling songs, and karyotypes. Nine previously described species are redescribed: N. carinata, N. castanea, N. convexa, N. diabolica, N. extincta, N. macneilli, N. propsti, N. sierranus, and N. steindachneri, and twelve new species are described: N. ambagiosa sp. n., N. arborea sp. n., N. cascadia sp. n., N. duplocantans sp. n., N. inversa sp. n.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 1,047 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Hybridization in particular, detected through mito-nuclear discordance (Gompert et al 2008), may be expected among sympatric lineages that are reproductively isolated through prezygotic barriers such as calling song (e.g. Cole et al 2021;Wade et al 2015). While topological support varied between nDNA and mtDNA datasets , namely poor resolution of the Okanagana ingroup with slower-evolving nuclear genes (see Wade et al 2015), mito-nuclear discordance was generally not observed and resolution in concatenated analyses was strong (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization in particular, detected through mito-nuclear discordance (Gompert et al 2008), may be expected among sympatric lineages that are reproductively isolated through prezygotic barriers such as calling song (e.g. Cole et al 2021;Wade et al 2015). While topological support varied between nDNA and mtDNA datasets , namely poor resolution of the Okanagana ingroup with slower-evolving nuclear genes (see Wade et al 2015), mito-nuclear discordance was generally not observed and resolution in concatenated analyses was strong (Figs.…”
Section: Discussionmentioning
confidence: 99%